Excellent response of rituximab and bendamustine in elderly patient with relapsed diffuse large B-cell lymphoma: a case report - Wiwiek Probowati; Merari Panti Astuti; Bambang Purwanto Utomo; Mardiah Suci Hardiyanti; Ibnu Purwanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Rituximab in combination with cyclophosphamide, doxorubicin, vincristine,and prednisone (R-CHOP) is currently the most widely used first-line therapyfor aggressive B-cell lymphomas. However, many patients, including thosewith organ dysfunction, may not tolerate the toxicities associated with thisregimen. Recent data from the phase III study group indolent lymphomas(StiL) non-Hodgkin lymphoma (NHL)-1 trial suggested that bendamustine plusrituximab were superior in effectiveness and tolerability compared to R-CHOPin the treatment of indolent and mantle cell lymphomas. Preliminary studyhas indicated the effective use of bendamustine alone or in combination inthe treatment of aggressive B-cell lymphomas as well. A 70-year-old malewith heavily treated relapsed diffuse large B-cell lymphoma (DLBCL) showedcomplete remission (CR) after receiving 8 cycles of rituximab in combinationwith bendamustine as 3rd line treatment. Bendamustine has demonstratedconsiderable efficacy and well-tolerated therapy in relapsed DLBCL patients.Our case report demonstrated that treating patients with bendamustinebasedregimen, even in the setting of organ impairment and elderly is safeand effective. Given the increasing evidence of its effectiveness, furtherinvestigation of bendamustine’s safety and tolerability aspects in specialgroups is recommended such as those with renal impairment.